KETELADANAN GURU AGAMA DALAM MEMBENTUK AKHLAKUL KARIMAH DI MIN 2 KOTA SURABAYA - Huda, Masrur; Zamroni, Miftachul; Wiyani, Sri (Universitas Islam Darul 'Ulum Lamongan, 2024)
The teacher's example has an important meaning in the educational process and is the most effective concrete example at MIN 2 Surabaya City. The central figure in MIN 2 Surabaya City is the key to the success of the noble character formation there. In this case Arif Mustofa has an important role in the success of education at MIN 2 Surabaya City. So it is very important to do research and record the uniqueness that has happened so far at MIN 2 Surabaya City.